The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1440-6047.11.s.7.4.x
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Estradiol epoxidation as the molecular basis for breast cancer initiation and prevention

Abstract: Epidemiological and animal studies have indicated that 17beta-estradiol (E2) is involved in breast cancer; however, the mechanism is unclear. We found that E2 could be activated by epoxidation, resulting in its ability to inhibit nuclear DNA-dependent RNA synthesis, and to bind DNA, forming DNA adducts both in vitro and in vivo. Because epoxidation is required for the activation of many chemical carcinogens, including benzo(a)pyrene, 7,12-dimethylbenz(a)anthracene and aflatoxins, we proposed previously that E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
1
1
0
3
Order By: Relevance
“…These reports are related indirectly to tumorigenesis, such as FSH producing adenoma (Tashiro et al 2000;Maruyama et al 2005;Roberts et al 2005). Other researchers have also reported a relationship between estrogen exposure and the risk of breast cancer (Yu 2002;Edlich et al 2005;Yager and Davidson 2006). Here, we present indirect evidence of hormone-induced tumorigenesis.…”
Section: Discussionsupporting
confidence: 62%
“…These reports are related indirectly to tumorigenesis, such as FSH producing adenoma (Tashiro et al 2000;Maruyama et al 2005;Roberts et al 2005). Other researchers have also reported a relationship between estrogen exposure and the risk of breast cancer (Yu 2002;Edlich et al 2005;Yager and Davidson 2006). Here, we present indirect evidence of hormone-induced tumorigenesis.…”
Section: Discussionsupporting
confidence: 62%
“…Epidemiological studies performed on animals indicated that 17 beta-estradiol (E2) was linked to breast cancer. It is known that E2 can be activated by epoxidation and that it is surely capable of inhibiting DNA synthesis for DNA- binding and adduct formation ( in vivo and in vitro) , playing an important role as a mammary carcinogenesis promoter [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esto significa que el efecto protector de la ovariohisterectomía disminuye rápidamente después de los primeros años de vida. Los estrógenos se pueden activar por epoxidación, lo que daña el dna e iniciará el proceso de carcinogénesis mamaria (Yu, 2002). Ninguna de las pacientes analizadas en esta investigación se castró antes de su primer celo, lo que permitió que su tejido mamario estuviera expuesto a una influencia hormonal significativa a lo largo de sus vidas.…”
Section: Discussionunclassified
“…Algunos factores de riesgo asociados con tumores de glándula mamaria son el género y la raza. Las hembras no castradas son las de mayor riesgo debido "al tropismo por la glándula mamaria que presentan los estrógenos naturales" (Yu, 2002). Asimismo, estudios epidemiológicos han descrito mayor susceptibilidad en razas de talla pequeña, entre ellas la Poodle, Maltés, Chihuahua, Cocker Spaniel, Springer Spaniel Inglés, Beagle, Yorkshire Terrier, Bichon Frisé, Springer Spaniel, Irish Setter y Pastor Alemán (Bronden et al, 2010).…”
unclassified